Mathematical modeling of thread-annular flow - Yiiong, Siew Ping (2010)
The axial thread-annular flow between two cylinders, where the inner cylinder is in a slightly eccentric position and moving at a constant velocity, is studied. we are particularly interedted on the mathematical modeling of the thread injection by considering the incompressible and steady flow between eccentric cylinders. The mathematical modeling of this application is presented using non-dimensional Navier-stokes equations and the governing equation is solved analytically. a comparison between concentric basic flow, which is considered by Walton (2003), and eccentric basic flow is made. It is found taht there is difference between concentric and eccentric basic flows.